Kewenangan Penetapan Pembatasan Sosial Berskala Besar Oleh Pemerintah Pusat Dalam Perspektif Undang-Undang Nomor 9 Tahun 2015 Tentang Perubahan Kedua Atas Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Regarding health issues, it is included in the concurrent government function related to basic services as referred to in Law Number 23 of 2014 concerning Regional Government. Not included in the affairs of absolute government. So the initial policy carried out by the Regional Government was a form of implementation of regional autonomy in the rhetoric of Law Number 23 of 2014 concerning Regional Government, because regional autonomy in the sense is the rights, powers and obligations of autonomous regions to regulate and manage government af-fairs and the interests of the local community. in accordance with the Prevailing Laws.This type of research is normative legal research, where this research focuses on legal principles that exist in legislation. The data source used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection tech-nique in this research is the literature review method, after the data is collected then it is ana-lyzed to draw conclusions.From the research results, it is concluded that, First, health problems are a mandatory government affair, but if in normal conditions, the Covid-19 issue is an emergency situation, in this case it is more centralized and constructed by the Central Government. So that the responsi-bility lies with the Central Government, because the Government has determined that Covid-19 is a national disaster.So that the determination of the PSBB is the authority of the Central Govern-ment. Second, mandatory government affairs related to basic services consist of six functions, one of which regulates health problems. Covid-19 is a pandemic so that it is declared an ex-traordinary public health incident, causing health hazards across regions or countries.Keywords :Regional Autonomy - PSBB - Unitary State